Autonomic dysfunction and migraine: Assessed by time series analysis of heart rate variability - Akter, Tahmina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2018)
Background: Migraine is associated with autonomic nervous system dysfunction with reduced heart rate variability (HRV). Objective: To assess the cardiac autonomic function in migraine patients. Methods: This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University during 2013. Cardiac autonomic nerve function of 60 newly diagnosed untreated migraine patients aged 15-30 years, both male and female was assessed by analyzing time domain measures of HRV. Thirty age, sex, BMI matched healthy control were also assessed and compared. The diagnosed migraine patients were selected from the out patient department of Neurology, BSMMU, Dhaka. The HRV parameters were recorded by a 4 active channels, RMS polyrite-D. For statistical analysis, Independent Sample t-test was used. Results: Resting pulse rate, mean heart rate were found significantly higher and mean R-R interval, SDNN, RMSSD were significantly lower in all patients with migraine than those of healthy control. Conclusion: Autonomic dysfunction characterized by impaired cardiac vagal tone was associated with migraine. Bangladesh Soc Physiol. 2017, December; 12(2): 57-60